2021
DOI: 10.2147/hiv.s336647
|View full text |Cite
|
Sign up to set email alerts
|

ART Adherence Among People Living with HIV Seeking Services from Public Health Facilities in Western Ethiopia

Abstract: Background The burden of COVID-19 is more severe among the elderly and patients affected with chronic medical conditions like diabetes, cardiovascular diseases, and HIV/AIDS. There is no study regarding the level of adherence to antiretroviral therapy (ART) during the time of COVID-19 in Ethiopia. So, this study aimed to assess the level of HIV positive patient’s adherence to ART treatment and associated factors in Nekemte public health facilities, Western Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In this study, older age (≥34-year old) was not associated with high ART adherence (AOR = 2.108; 95% CI: 0.703–6.319, p = 0.183). On the other hand, Tolossa et al ( 24 ) reported that the odds of non-adherence to ART were 3.41 times higher among patients younger than 25 years as compared to their counterpart (OR = 3.41, 95% CI: 1.26–9.21) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, older age (≥34-year old) was not associated with high ART adherence (AOR = 2.108; 95% CI: 0.703–6.319, p = 0.183). On the other hand, Tolossa et al ( 24 ) reported that the odds of non-adherence to ART were 3.41 times higher among patients younger than 25 years as compared to their counterpart (OR = 3.41, 95% CI: 1.26–9.21) ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women have been known to have better health seeking behaviour [ 44 , 45 ] and better adherence to treatment than men [ 46 ] which would consequently lead to improved viral suppression [ 47 ]. Similarly, adults have been shown to be more likely to be adherent to ART compared to adolescents and young persons [ 48 50 ], while MMD and community-based ART models are proven strategies for improving ART adherence [ 22 , 23 , 32 ]. Targeted program interventions to these affected socio-demographics may enhance viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…45 A study from Ethiopia also showed the risk of developing TF was higher among young age groups. 43 This could be due to the high association between younger age and poor drug adherence 46,47 which might lead to the least viral suppression. 29,47 A study from Gondar-Ethiopia showed there is no association between the age of patients with SLART failure.…”
Section: Discussionmentioning
confidence: 99%